Pengaruh Penggunaan Al-Qur’an Digital Terhadap Intensitas Membaca Al-Qur’an Pada Mahasiswa Prodi Pendidikan Agama Islam Angkatan 2021 IAIN Syaikh Abdurrahman Siddik Bangka Belitung - Zuhdi, Herman; Febrino, Febrino; Iskandi, Iskandi (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This research is undermined by the fact that the ownership rate of the Qur'an among the students of Islamic Religion Education belonged to the high category of 60% of the total number of students in Islamic Religion Education in 2021. With the advancement of the era, technology has evolved rapidly and advanced, including the digital Qur'an that can be obtained on mobile phones, computers, and so on. He will be able to read the Qur'an in a way that will help him understand the truth. To find out whether the use of the digital Quran has an impact on the reading intensity of the Quran among the students of Islamic Religion Education 2021. This research is quantitative. Quantitative research is research that collects data and analyzes data in the form of numbers used to explain the results of research. In this study, 112 students were chosen at random using the Slovin formula. The analysis techniques used in this research are descriptive statistics and simple linear regression analysis. The results of this study show that the reading intensity of the Quran among students in Islamic Religion Education falls into the middle category with a percentage of 68.8%. Besides, there is an influence between the variable of the use of the digital Quran and the variables of the reading intensification of the Qur’an in students of Islamic religion education in 2021. The thitung > ttable value of 2,592 > 1,9818 demonstrates this. From the summary model table, it can be concluded that the influence of free variables on the bound variables in this study is 0.058 and multiplied by 100% to obtain a result of 5.8%. It can be inferred that the use of digital Al-Qur’an influences the intensity of reading Al-Qur'an in prodi students of Islamic Religion Education in 2021 by a factor of 5.8%.